INTERNAL MARKETING'S RIPPLE EFFECT: SHAPING ORGANIZATIONAL SUCCESS THROUGH CUSTOMER SATISFACTION - Diallo, Thierno Mamadou (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
The concept of internal marketing, originating in the 1980s, underscores the significance of fostering positive internal relations across organizational levels. Primarily driven by the need to augment service quality within service sectors, internal marketing emphasizes the pivotal role of motivated employees (internal customers) who possess an understanding of customer needs. This paper delves into the evolution of internal marketing in tandem with external marketing and service quality concepts. A salient attribute of services is the direct interaction between internal and external customers, with customer-oriented behaviors playing a crucial role in these interactions. Aiming to enhance service quality and external customer satisfaction, this study underscores the importance of aligning staff (internal customers) commitment with company goals and customer-centric behaviors. Subsequent research has substantiated a strong correlation between the contentment of internal customers and the satisfaction of external customers, further highlighting the interdependence of these two facets (Piercy, 1999; Rafiq and Ahmed, 1993). This research contributes to the ongoing discourse on internal marketing, shedding light on its integral role in bolstering overall customer satisfaction and service quality